2014
DOI: 10.1208/s12249-014-0142-7
|View full text |Cite
|
Sign up to set email alerts
|

The Practicality of Mesoporous Silica Nanoparticles as Drug Delivery Devices and Progress Toward This Goal

Abstract: Abstract. Mesoporous silica nanoparticles (MSNs) have been proposed as drug delivery devices for approximately 15 years. The history of in vitro studies has been promising, demonstrating that MSNs have the capability for stimulus-responsive controlled release, good cellular uptake, cell specific targeting, and the ability to carry a variety of cargoes from hydrophobic drug molecules to imaging agents. However, the translation of the in vitro findings to in vivo conditions has been slow. Herein, we review the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…For this reason, Si-NPs have been widely used in gene transfection, drug delivery, biosensing and bioimaging [164166]. It has been observed that these nanostructures promote osteoblast differentiation through autophagy stimulation [167].…”
Section: Targeting Autophagy With Metal-based Nanoparticles As Therapmentioning
confidence: 99%
“…For this reason, Si-NPs have been widely used in gene transfection, drug delivery, biosensing and bioimaging [164166]. It has been observed that these nanostructures promote osteoblast differentiation through autophagy stimulation [167].…”
Section: Targeting Autophagy With Metal-based Nanoparticles As Therapmentioning
confidence: 99%
“…For compound 89,t he authors hypothesized that the quinone TML moiety might act as as econd antibacterial warhead inhibiting thiolcontaining enzymes, and this leads to ad ual-acting hybrid,a s illustrated in the box in Scheme 18. [129][130][131][132] In their report, Wu and co-workers modify the surfaces of the MSNPs with 3-aminopropylsiloxanes Scheme17. NQO1-sensitive quinone-type TML moieties have also been used for the stimuli-responsive controlled releaseo fc ompounds from modified liposomes and polymer-based nanoparticles.I n2 008, McCarley and co-workersr eported the synthesis of quinoneT ML dioleyl phosphatidylethanolamine (Q-DOPE) lipid 93 (Scheme 19).…”
Section: Quinone-oxidoreductase-sensitive Tml Systemsmentioning
confidence: 99%
“…Different templating agents such as ionic surfactants, pluronic surfactants, and neutral block copolymers are further used to influence pore size and arrangement as well the MSN's general shape and size. [54] The use of polyelectrolyte gatekeepers, supramolecularnanovalves, pH-sensitive linkers, and acid-decomposable inorganic gatekeepers with MSNs to form a pH-responsive release system has also been studied to further enhance MSN delivery for the treatment of diseases such as cancer. [55] MSN-based systems have also been studied for the research of other stimuli-responsive delivery mechanisms for both endogenous stimuli such as enzymes and glucose and exogenous stimuli light and magnetics.…”
Section: Mesoporous Silica-based Nanoparticlesmentioning
confidence: 99%
“…[56] More research is still being conducted that focuses on the safety, biodegradability, pharmacokinetics, and biodistribution of MSNs. [54] Semiconductor Quantum Dots Semiconductor quantum dots have become attractive to researchers for siRNA delivery because of their usefulness in molecular imaging as fluorophores. As carriers, they exhibit biocompatibility.…”
Section: Mesoporous Silica-based Nanoparticlesmentioning
confidence: 99%